How to define pulmonary hypertension due to left heart disease. Issue 2 (12th May 2016) - Gerges, Mario; Gerges, Christian; Lang, Irene M.
Current 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) guidelines for the diagnosis and treatment of pulmonary hypertension (PH) [1, 2] have adopted new insights in the understanding of PH due to left heart disease (PH-LHD, group 2). Pulmonary vascular disease in heart failure comprises increased RV afterload, poor RV-PV coupling and worse survival http://ow.ly/4n622h